Face hallucination with application in far distance face recognition - Xu, Xiang (Curtin University, 2014)
In this thesis, faces captured in far distances are investigated. Face enhancement algorithms are studied. Hallucinating faces in holistic model and patch-based model are analysed respectively. The advantages and disadvantages of both models are discussed. An innovative holistic model and patch-based model are proposed separately. More investigation in practical surveillance environments are carried. And a new far face recognition model is proposed. Experiments demonstrate the improvement of proposed approaches.